Practice and Match Workload Characteristics of Elite Men’s Ice Hockey - Steven Nightingale; Jonathan Hughes; Mark De Ste Croix; Craig Pfeifer (International Journal of Strength and Conditioning, 2024)
The purpose of this study was to record and present data related to the external workload demand of elite male ice hockey players, in both matches and practices, including the differences between positions, as well as time on ice values for the population. External workload monitoring was performed using a CatapultTMinertial measurement unit system and data was collected for the duration of one full season in the Kontinental Hockey League (Russia). The study found forwards had significantly higher (p ≤ 0.05) absolute and relative values in both games and practices for most metrics, when compared to defensemen, and regardless of position, games had significantly higher workload demand than practices. Furthermore, defensemen had significantly higher (p ≤ 0.05) time on ice values than forwards. Ice time was not spread evenly between players of the same position, but was consistent for each individual athlete. The findings can be used by coaches to assist in the planning of on-ice training to optimize player performance and readiness.